Trihalomethane (THM) reduction in Istanbul water treatment plants - (:unkn) unknown (IWA Publishing, 2001)
This paper describes trihalomethane reduction in an Istanbul drinking water plant. The total THM levels (TTHM) could be controlled by decreasing the post-chlorination doses. After the commencement of the pre-ozonation process, pre-chlorination was terminated and a sudden drop of THM values in the effluent of the plant was observed. A predictive model that gives a good fit to the observed TTHM levels during the 7 months operation of the plant with and without the pre-ozonation process was presented.
Keywords: Chlorination; Chloroform; Modelling; Ozonation; Triholamethanes reduction; Water treatment